2008
DOI: 10.1080/02699050701810688
|View full text |Cite
|
Sign up to set email alerts
|

Personal digital assistants as cognitive aids for individuals with severe traumatic brain injury: A community-based trial

Abstract: A brief training intervention utilizing PDAs as cognitive aids is associated with improved self-ratings of performance in everyday life tasks among community-dwelling individuals with severe TBI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(51 citation statements)
references
References 24 publications
1
49
0
1
Order By: Relevance
“…Even if the COPM has good test-retest reliability [42], the large positive change in the scores on the COPM may indicate a placebo effect [20], or a therapeutic effect of the many contacts with the OT during intervention. As the same OT performed both the evaluations and interventions it is also possible that this affected the ratings in a positive direction.…”
Section: Methodological Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even if the COPM has good test-retest reliability [42], the large positive change in the scores on the COPM may indicate a placebo effect [20], or a therapeutic effect of the many contacts with the OT during intervention. As the same OT performed both the evaluations and interventions it is also possible that this affected the ratings in a positive direction.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…To the best of our knowledge, only one study has used unmodified handheld computers off-the-shelf to compensate for disabilities in people with ABI [20]. The use of a standard mobile phone was effective in assisting people by reminding them about their appointments, daily routines and medication [21].…”
Section: Introductionmentioning
confidence: 99%
“…Gentry, Wallace, Kvarfordt, & Lynch, 2010). However, this approach does not always involve hands on use by the learner themselves.…”
Section: Mobile Computing/learningmentioning
confidence: 99%
“…In addition they often have multiple functions and applications that can support memory, such as calendars and voice recorders [1,4]. A number of studies have shown that electronic compensatory memory aids, such as pagers [12,13], mobile phones [14,15], PDAs [1,10,16,17] and smartphones [18,19,20] can be effective in supporting prospective memory in adults with brain injury, by helping them to remember and complete everyday tasks. A recent systematic review also concluded that external assistive devices reduce forgetfulness in adults after traumatic brain injury (TBI) or stroke [21].…”
Section: Introductionmentioning
confidence: 99%